EFFECTIVENESS OF TECHNOLOGICAL UPGRADES ON THE ENHANCEMENT OF GUEST EXPERIENCE AT MC HOTEL FAIRVIEW, QUEZON CITY (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
The hospitality industry is undergoing significant changes driven by rapid technological advancements and rising guest expectations. While these innovations offer opportunities to improve guest satisfaction and streamline operations, they also pose challenges in terms of implementation costs, system integration, and employee adaptability. This study evaluates the effectiveness of recent technological upgrades at Mc Hotel Fairview in Quezon City, with a specific focus on housekeeping services and their contribution to enhancing the overall guest experience. This study employs a quantitative descriptive research design to assess the impact of technology on guest satisfaction. Data are collected through a survey questionnaire administered to 30 purposively selected guests at Mc Hotel Fairview. Purposive sampling is used to ensure a diverse representation of guest demographics, experiences, and perspectives. The survey measures guest perceptions of technological features such as room service ordering, internet connectivity, and digital access systems, providing a detailed understanding of how these tools influence the guest experience. The majority of respondents (73%) were aged 21 to 25, indicating a predominantly younger guest demographic. Participants expressed high satisfaction with technological upgrades, particularly with the ease of room service requests, keyless entry systems, and stable Wi-Fi access. While amenities and digital features were generally well-received, guests noted areas for improvement, including room pricing, staff proficiency in using new technologies, and the consistent functionality of in-room devices. The findings underscore the importance of strategic technology integration in enhancing the guest experience. The study recommends the development of a user-friendly mobile application, the implementation of AI-powered chatbots for guest assistance, and the provision of high-speed internet access. Additionally, improving staff training, upgrading room amenities, and refining room service operations are essential for sustained guest satisfaction. Establishing strong feedback mechanisms, maintaining strict cleanliness standards, and launching targeted marketing campaigns can further improve guest retention and brand loyalty.
Keywords: guest experience; technological upgrades; hospitality management; mc hotel fairview; digital services; housekeeping; hotel technology; guest satisfaction; mobile app integration; ai chatbots